Penyuluhan Protokol Kesehatan COVID-19 Di Warga GKJTU (Gereja Kristen Jawa Tengah Utara) Kembang Kota Salatiga - Endang Susilowati; Nur Sri Atik (Pelita Medika, 2021)
Background: The Covid-19 pandemic has entered a new chapter of a new life order or a new normal. However, the rate of Covid-19 transmission is still quite high, especially in the City of Salatiga. The discovery of residents who have not carried out proper health protocols is one of the factors causing the high transmission of Covid-19. This requires a socialization effort in the form of counseling activities in order to prevent the transmission of Covid-19. This activity was carried out within the North Central Java Christian Church (GKJTU) Kembang Kota Salatiga. The aim of this activity is to increase the awareness of church members of the importance of correct health protocols and changes in behavior in implementing health protocols. Method: The methods used include counseling, publication through the WA Group of Church Citizens and monitoring and evaluating the application of the Covid-19 health protocol discipline. Result: The result of community service is increased awareness of church members, as evidenced by the fact that every week of worship there is a change in behavior in implementing health protocols, especially in wearing masks (materials and how to wear masks). Conclusion: Outreach increases the resilience of citizens in implementing health protocols.